Evaluasi Penggunaan dan Pelaporan Dana Bantuan Operasional Sekolah Pada SD Negeri 1 Gading Kembar - Nikmatussiama, Silvia Laila; Sodik, H. M.; Zainudin, Zainudin (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2024)
School Operational Assistance (BOS) funds are one of the crucial elements in improving the quality of education in Indonesia. The use and reporting of BOS funds are in the spotlight in an effort to ensure efficiency, transparency, and accountability in their utilization. In Government Accounting Standard Statement No. 01 (PSAP 01) on the Presentation of Financial Statements, transfers are receipts/expenditures of money from one reporting entity to another reporting entity, including equalization funds. A qualitative research approach is a research methodology that aims to understand the meaning and interpretation of social phenomena. The source of funds obtained from the central and local governments is the BOS Fund in the submission of the School Activity and Budget Plan (RKAS). According to the RKAS, the transfer of funds from the government account to the school amounted to Rp.94,050,000.